Optimizing the Role of Social Media for Fisheries Business Development (Case Study in the Middle of Covid 19 Pandemic in West Java) - Atikah Nurhayati; Indah Riyantini; Isni Nurruhwati; Isah Aisah (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2021)
The spread of the Covid 19 outbreak felt its impact in the fisheries sector. The spread of Corona Virus has brought new challenges and risks in social life, including fisheries businesses. Fishery business practitioners, namely fishermen, fish cultivators, fishery product processors and fishery product marketers, experience logistical and marketing problems. Some indications of the impact of the Covid-19 pandemic are evident in the fisheries business. These indications are a decrease in the price of fishery products, a logistic system that cannot run normally, and a decrease in demand for fishery products, all of which impact on the household income of the fishery business. The disruption of distribution channels between businesses and consumers due to restrictions on human mobility that is applied to overcome the Covid 19 outbreak is the root cause. Regional quarantine as well as large-scale social restrictions do not prohibit mobility in the transportation of goods, but in reality these restrictions significantly impede the traffic of fishery products. This is reminiscent of the implementation of the 4.0 revolution in the fisheries and marine sector, where fisheries and marine businesses including fish farmers to innovate in the use of automation tools that are controlled from smartphone applications. With digital applications, cultivation can use it to anticipate during current conditions, when the Covid 19 pandemic occurs, where market access is directly restricted which can be circumvented by online marketing where producers and consumers do not make transactions directly. This reserach  aims to analyze the optimization of the role of social media for the development of fisheries business case studies in the middle of the Covid 19 pandemic in West Java. Research time is from February to May 2020. The research method used was a survey method. The data used are primary and secondary data. Primary data were obtained by taking the technique of non-probability sampling respondents to 40 respondents of fisheries businesses. The analytical tool used in this reserach  is non-parametric statistics with Friedman and Kendalls using twigs to scale. Based on the results of research, the level of knowledge of fisheries business operators regarding handling of Covid 19 averages 70% of knowing, understanding and implementing health protocols in carrying out daily activities, the role of social media is high for fisheries business actors consisting of fishermen, fish cultivators, fishery product processors and marketer of fishery products. Social media used include Instagram, Short Message Service (SMS), Websites, Blogs, Facebook and Whatsapps. The most optimal use of social media activities is carried out by fishery product marketers via Whatsapps. and Instagram.